Considerations about Materiality and the Medial Processes in the Puppet Company “Die Klappe. Das Kabarett an Fäden” - Orduño Bucio, Rodrigo (Intermédialités / Intermediality, 2024)
This text collects some considerations of the work of the German puppet company “Die Klappe. Das Kabarett an Fäden” in the postwar period. From the study of a puppet, its morphology and its stage performance, the medial processes set in motion and promoted by its material constitution are explored, including the energetic flows that incite the act of embodiment framed by the register of the cinematographic camera. I consider the above as a reflection of the media incorporation promoted by the neo-avant-garde in the puppet theater.